Evaluation of the pathogenicity of a rescued avian metapneumovirus subtype B strain in China - Yu, Zekun; Jiang, Chengyuan; Guo, Aili; Wang, Haimin; Yuan, Chen; Sun, Tairan; Song, Qinye (Frontiers in Veterinary Science, 2025)
Avian metapneumovirus sub-type B (aMPV-B) is now widespread in China, causing significant declines in egg production among layer hens. However, the characteristics of sub-clinical infections and co-infections often resulted in low viral isolation rates, impeding research on its pathogenic mechanisms. To clarify the pathogenicity of Chinese aMPV-B field strains, we generated a strain B1 using reverse genetics and evaluated its pathogenicity in specific-pathogen-free (SPF) chickens. The complete 13,516 nt genome of strain B1 was assembled through segmented sequencing and alignment, exhibiting 96.5 to 98.7% sequence homology with prototype sub-type B strains, and > 98.6% identity with Chinese isolates. The rescued strain B1 was generated using a three-plasmid rescue system. In Vero cells, the rescued B1 induced characteristic syncytium formation, reaching the peak of the viral titer at 5 days post-infection (dpi). SPF chickens inoculated intranasally exhibited mild clinical signs dominated by nasal scratching and head shaking. The symptoms persisted for approximately 10 days, with the most severe at 5 days post-challenge (dpc). Oropharyngeal viral shedding peaked at 3 dpc and lasted around 7 days, and the predominant viral replication was in the upper respiratory tract, causing mucosal damage to nasal turbinates. Moreover, a challenge dose >102.0 TCID50 elicited pronounced shedding peaks with similar shedding kinetics but low-dose viral challenge prolonged the viral incubation period. Under the 104.0 TCID50 challenge dose, SPF chickens of different week-ages exhibited consistent virus shedding trends. This study advances the understanding of pathogenic features of Chinese aMPV-B strain and provides critical data for developing targeted control measures.